PsycEXTRA Dataset 2009
DOI: 10.1037/e578562012-003
|View full text |Cite
|
Sign up to set email alerts
|

Prospective memory in the nursing environment: Effects of type of prospective task and prospective load

Abstract: The nursing environment is replete with event-based and time-based prospective memory (PM) tasks (i.e. high prospective load). However, the effects of time-based prospective load, prospective load in naturalistic settings, and prospective load with unique retrospective components for each PM task remains unknown. To address this gap, the current study used a mockup patient room setting to examine the effects of PM type (event-based or time based) and prospective load (1 vs. 4 tasks) with unique prospective and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The tasks for this study have been adapted from a prior PM study that used data entry in the context of a medical environment (Fink, Pak & Battisto, 2009). The primary task is to quickly and accurately input names, addresses, and phone numbers contained on paper forms into computer-based forms.…”
Section: Taskmentioning
confidence: 99%
“…The tasks for this study have been adapted from a prior PM study that used data entry in the context of a medical environment (Fink, Pak & Battisto, 2009). The primary task is to quickly and accurately input names, addresses, and phone numbers contained on paper forms into computer-based forms.…”
Section: Taskmentioning
confidence: 99%
“…A nurse 's work environment places heavy demands on both time-based and event-based PM. Examples of such PM tasks include remembering to communicate with other staff, giving medications at specific times, checking for new orders, attending meetings, bringing patients' requests, continuous monitoring of changing information, and resuming tasks [3,4]. Madadzadeh et al [5] reported that the workload is one of the most significant factors in nursing retention; measuring nursing workload reliability is the critical initial step to understanding the association between workload, nursing retention, and the safety and health of the patients [6].…”
Section: Introductionmentioning
confidence: 99%